Approximation of C0-Semigroups Generated by Differential Operators on the Unit Interval. (4th May 2017) - Mocanu, Gabriela; Raşa, Ioan
ABSTRACT: We consider the C 0 -semigroups generated on the spaces of continuous functions, respectively, square-integrable functions, by the differential operator The relationship between these semigroups as well as several qualitative properties of them is studied. We discuss the possibility of approximating the semigroups in terms of suitable iterations of positive linear operators.